2018
DOI: 10.1021/acs.orglett.8b00847
|View full text |Cite
|
Sign up to set email alerts
|

Direct Silyl–Heck Reaction of Chlorosilanes

Abstract: A nickel complex/Lewis acid combination effectively catalyzed the direct silyl-Heck reaction of chlorosilanes, which are key raw materials in the organosilicon industry, to give synthetically important alkenylsilane products. Trichlorosilanes, dichlorosilanes, and monochlorosilanes underwent the silyl-Heck reaction to afford the corresponding alkenylsilanes in high yields. In the reactions of dichlorosilanes, a single substitution occurred to give monoalkenylsilanes in a highly selective manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…Meanwhile, we also reported nickel‐catalyzed silyl‐Heck reaction of chlorosilanes . This research demonstrated 1) the first example of direct catalytic transformation of strong Si−Cl bonds (ca.…”
Section: Methodsmentioning
confidence: 70%
See 3 more Smart Citations
“…Meanwhile, we also reported nickel‐catalyzed silyl‐Heck reaction of chlorosilanes . This research demonstrated 1) the first example of direct catalytic transformation of strong Si−Cl bonds (ca.…”
Section: Methodsmentioning
confidence: 70%
“…Transition‐metal‐catalyzed cross‐coupling of halosilanes with various coupling partners are attractive methods to synthesize organochlorosilanes with various substituents selectively . Recent research in this field has been conducted by Watson et al ., who reported silyl‐Heck reaction with olefins as well as silyl‐Negishi coupling with organozinc reagents and silyl‐Kumada‐Tamao coupling with Grignard reagents of halosilanes (Scheme c).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vinylsilanes are valuable building blocks in organic synthesis and material chemistry because of their versatile characters, such as low toxicity, high stability, facile manipulations, and a variety of transformations . Accordingly, methods for the preparation of vinylsilanes have gained increased attentions from synthetic chemists, in which the hydrosilylation of alkynes was considered as a simple and straightforward method .…”
Section: Introductionmentioning
confidence: 99%